Made in YU 2015 - Mlekuž, Jernej; Petrović, Tanja (Kulturni spomin, 2016)
The book brings several essays on objects, atmospheres, moods, flavors and scents that marked the everyday life in the socialist Yugoslavia. The authors of individual chapters in Made in YU use these objects, atmospheres, moods, flavors and scents as lenses through which they observe practices and processes of significant restructurings and reframings of everyday, cultural, political and affective worlds in the post-Yugoslav societies.